1983
DOI: 10.1148/radiology.146.1.6849071
|View full text |Cite
|
Sign up to set email alerts
|

The value of computed tomographic metrizamide myelography in the neuroradiological evaluation of the spine.

Abstract: The diagnostic value of plain film metrizamide myelography (PFMM) was compared with computed tomographic metrizamide myelography (CTMM) in a study of 106 individuals who had undergone high-resolution computed tomographic scanning of the spine. CTMM provided more significant information than PFMM in 42 of 106 cases (40%), but showed no advantage over PFMM in 63 of 106 cases (59%). In 19 of the 42 cases (45%), PFMM was useful in directing the CT analysis to the appropriate region of pathology. In one patient, PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…A postmyelography CT examination can be advantageous, but not always as helpful as expected (5). There seem to be no previous studies where conventional CT and postmyelography CT examinations have been performed on the same day, i.e.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…A postmyelography CT examination can be advantageous, but not always as helpful as expected (5). There seem to be no previous studies where conventional CT and postmyelography CT examinations have been performed on the same day, i.e.…”
Section: Discussionmentioning
confidence: 96%
“…under equal conditions in regard to the general condition of the patient and the lumbo-ischialgic pain syndrome. Earlier investigators (5) have recommended a rotation of the patient for 360 degrees prior to the postmyelography CT examination in order to prevent layering of the contrast medium. In the present study the patients were instructed to remain supine until the examinations were concluded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…59 During the next several years, articles describing the efficacy of combining myelography with CT in a variety of pathologic conditions were published. 60 In the early 1980s, lumbar spine CT after IV contrast administration was used to aid in the diagnosis of degenerative disease, especially in the cervical spine, in the postoperative lumbar spine to differentiate recurrent disk from scar, and in tumors and inflammatory diseases of the spine. 8 Although the history of MR imaging dates back to the 1940s, the first commercial MR imaging scanner was introduced in 1980 and the first superconducting magnet was put in clinical use in 1981.…”
Section: Cross-sectional Imaging Of the Spinementioning
confidence: 99%